The ADHD book of lists a practical guide for helping children and teens with attention deficit disorders - Rief, Sandra F. (Jossey-Bass, 2015)
"The newly updated ADHD Book of Lists will be a comprehensive, reliable source of answers, practical strategies, and tools written in a convenient list format"--Provided by publisher.